2018
DOI: 10.1002/etep.2517
|View full text |Cite
|
Sign up to set email alerts
|

An artificial neural network-based solution to locate the multilocation faults in double circuit series capacitor compensated transmission lines

Abstract: During thunder storms, multilocation faults may occur at different locations in different phases of the 3 phase transmission lines at same or different time. This paper proposes an artificial neural network-based solution to locate the multilocation faults in double-circuit series capacitor compensated transmission lines (SCCTLs), unlike previous works that only locate the fault at single location. Although various fault location schemes have been proposed for normal shunt faults occurring at 1 location in SCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The majority of studies have been validated on shunt faults, while only a few have addressed the issues related to the multi-location (two-location) faults in TCSCTLs. The popular computational approaches used in the development of multi-location fault models include neural networks [10,11], fuzzy rule-based systems (FRS) [12,13], and support vector machines [14]. Among these methods, FRS is proven to be the most suitable method, followed by support vector machines and neural network techniques.…”
Section: Related Researchmentioning
confidence: 99%
“…The majority of studies have been validated on shunt faults, while only a few have addressed the issues related to the multi-location (two-location) faults in TCSCTLs. The popular computational approaches used in the development of multi-location fault models include neural networks [10,11], fuzzy rule-based systems (FRS) [12,13], and support vector machines [14]. Among these methods, FRS is proven to be the most suitable method, followed by support vector machines and neural network techniques.…”
Section: Related Researchmentioning
confidence: 99%
“…In the last decade, a vast number of research work have been reported on different aspects related to various faults in the area of underground power distribution system likely analysis of faults [25][26][27][28][29][30], adaptive fault [31][32][33], SC, OC and ground faults [34][35][36][37], detection [38,39], classification [40] and fault location [41][42][43][44][45][46], sustainable protection [47,48], noise monitoring [49], and for thermal test [50].…”
Section: Introductionmentioning
confidence: 99%
“…These days, the ANN approach [9][10][11] and fuzzy logic approach [12][13][14] also known as artificial intelligent (AI) techniques, have led to an improved output in terms of system robustness and a highly accurate network. Typically, the AI methods required feature extraction to extract important feature information for diagnostic purposes.…”
Section: Introductionmentioning
confidence: 99%